Steering the future of travel demand: an interview with Greg Marsden about building dialogues and changing practices. Issue 1 (2nd January 2022) - Hui, Allison; Marsden, Greg
ABSTRACT: With governments around the world committed to radically reducing greenhouse gas emissions by 2050, and transport-related mobilities making up a significant proportion of current carbon emissions, questions of how to change mobility systems have become a pressing concern. Yet the urgency of this challenge cannot be met with more of the same – particularly in terms of narrow discussions of behaviour change that fail to draw upon the wealth of relevant social scientific research. New methods of collaborating and bringing together communities – whether policymakers, academics, or publics – will also be key. Greg Marsden brings a particularly interesting set of perspectives to the question of what future travel demand might look like, and how we can change practices to get there. While currently a Professor of Transport Governance at Leeds University, Greg has spent significant periods working with policymakers – both within Transport for London and supporting the UK Parliament Transport Select Committee, which scrutinises the UK Department for Transport's (DfT) spending and policies. Our conversation looks at how spaces can be fostered for new ways of thinking, communicating and collaborating to address the challenge of rapidly decarbonising transport systems. Though largely focused upon the UK, the conversation highlights issues related to policy engagement, theory and evidence, and understandings of sharing that will have much wider relevance.